PKM KELURAHAN KESIMAN DALAM PENYELESAIAN PERMASALAHAN BANJIR DI LINGKUNGAN JALAN AKASIA - Putu Ayu Sriasih Wesna; Toto Noerasto Noerasto; Kadek Windy Candrayana M.T (Universitas Warmadewa, 2021)
The development of settlements in urban areas is getting higher, causing complex problems to arise. Population growth also affects the need for land. This condition occurs in a residential area on Jalan Akasia, Kesiman Village. There have been regulations in the form of Perda Perda No.27 of 2011 concerning Spatial Planning of Denpasar City of 2011-2031 and Perda of Denpasar City No. 5 of 2019 concerning buildings. The regulation regulates the Basic Building Coefficient (KDB) so that infiltration areas and canal boundaries are available to prevent construction that reduces the canal's dimensions. The current condition of settlements does not comply with these regulations so that the lack of infiltration areas impacts the occurrence of floods. As well as a reduction in the dimensions of the channel due to development by the community. To overcome these problems, it is necessary to socialize the application of development rules in the study area to obtain a picture of the problem from the regulatory side. Meanwhile, from a technical point of view, this PKM reviews the condition of the channel and flood points, which is then outlined in a map of the channel and flood area on Jalan Akasia, Kesiman Village. In terms of regulations, socialization needs to be carried out so that people are aware of the importance of implementing KDB and channel boundaries in correlation to flood events.